On the Identity and Character of Serbian Interwar Architecture (1918–1941) - Stefanović, Tadija B. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
This paper offers a presentation and interpretation of Serbian architecture between 1918 and 1941, whose creative span ranged between artistic-aesthetic and political-ideological utopias. Within this space numerous individual creators acted, authors of epochal achievements, as well as those creative forces that found their affirmation in social collectivism in the interwar architecture. The specific artistic character of this architecture was founded on striking stylistic contrasts, on its social function and on ideological factors, which formed the basis for an authentic cultural and artistic profile of Serbian interwar architecture. The aesthetic approach is based on the value parameters, spiritual constants, and social role of architecture, as its most characteristic features. Although disparate in both content and quality, Serbian interwar architecture reflects a unique and distinctive identity. Its varied characteristics were composed into the complex picture offered by the interwar architecture, as a credible indicator combining the prevailing features of Serbian interwar society, the builder’s attitudes as well as tastes of the commissioners. The importance of interwar architecture derived from the process of character interpretation, which constructed the visual identity of interwar architecture through the mechanisms of art and culture.